Development of E-Learning Statistics Learning Models in UIN Sultan Maulana Hasanuddin Banten - Wibowo, Eko Wahyu; Suriani; Siang, Jhoni Lagun; Dahlan, Jafar (International Journal of Psychosocial Rehabilitation, 2020)
In general, this study aims to produce a model of statistical education learning with elearning in order to improve student understanding. This research is a Research and Development (Research and Development). Research and development are a research that is designed to develop a new product and or can complement a product that has been done with steps that can be accounted for. Educational Statistics Learning Model with e-learning at UIN Sultan Maulana Hasanuddin Banten is feasible to use. The Education Statistics learning model with e-learning at UIN Sultan Maulana Hasanuddin Banten effectively improves student learning outcomes.